A charge reversal nano-assembly prevents hepatic steatosis by resolving inflammation and improving lipid metabolism - Haoyu Wang; Sheng'e Su; Xin An; Yuan Xu; Jiacheng Sun; Mingming Zhen; Chunru Wang; Chunli Bai (Bioactive Materials)
Lipid metabolism imbalance combined with over-activated inflammation are two key factors for hepatic stestosis. However, on-demand anchoring inflammation and lipid metabolism disorder for hepatic stestosis treatment has yet to be realized. Here we propose a charge reversal fullerene based nano-assembly to migrate hepatic steatosis via inhibiting macrophage-mediated inflammation and normalizing hepatocellular lipid metabolism in obesity mice. Our nano-assembly (abbreviated as FPPD) is comprised of electropositive polyetherimide (PEI), charge-shielded dimethylmaleic anhydride (DMA), and poly(lactic-co-glycolic acid) (PLGA), which provides hydrophobic chains for self-assembly with anti-oxidative dicarboxy fullerene poly(ethylene glycol) molecule (FP). The obtained FPPD nano-assembly owns a charge reversal ability that switches to a positive charge in an acidic environment that targets the electronegative mitochondria both in pro-inflammatory macrophages and steatosis hepatocytes. We demonstrate that the anti-oxidative and mitochondria-targeting FPPD notably reduces inflammation in macrophages and lipid accumulation in hepatocytes by quenching excessive reactive oxygen species (ROS) and improving mitochondrial function in vitro. Importantly, FPPD nano-assembly reveals a superior anti-hepatic steatosis effect via migrating inflammation and facilitating lipid transport in obesity mice. Overall, the charge reversal nano-assembly reduces over-activated inflammation and promotes lipid metabolism that provides an effectiveness of a multi-target strategy for hepatic steatosis treatment.